Country-level politics around the SDGs: Analysing political will as a critical element of the Mid-Term Review of the 2030 Agenda and the SDGs - Marianne Beisheim (Stiftung Wissenschaft und Politik (SWP), 2023)
The SDG Summit will take place on 18-19 September 2023 in New York. UN Secretary-General António Guterres has called it the 'centrepiece' of the UN's work this year. Numerous reports for this year's mid-term review of the 2030 Agenda and the SDGs will lament the 'lack of political will' to implement the SDGs. This research paper addresses the lack of analysis of country-level politics around the SDGs by assessing the political priorities of local elites in eleven countries. Alongside the specific findings for these countries, we present overarching conclusions on the significance of country-level politics for SDG implementation. Analysing political will and considering country-level constraints should be part of the mid-term review and inform the outcome of the summit.
Keywords: 320; 2023 SDG Summit; 2030 Agenda; Sustainable Development Goals (SDGs); Global Sustainable Development Report (GSDR); Belarus; Brazil; China; Egypt; India; Kenya; Republic of Korea; Russian Federation; South Africa; State of Palestine; Sudan